Alkoxy base-mediated selective synthesis and new rearrangements of 1, 2, 4-triazolodipyrimidinones. Issue 8 (22nd February 2017) - Pyatakov, Dmitry A.; Astakhov, Alexander V.; Sokolov, Andrey N.; Fakhrutdinov, Artem N.; Fitch, Andrew N.; Rybakov, Victor B.; Chernyshev, Vladimir V.; Chernyshev, Victor M.
Graphical abstract: Highlights: Selective base-mediated cyclization of enaminoesters into triazolodipyrimidinones. A new cascade rearrangement of the triazolodipyrimidinones. An experimental and DFT study. Abstract: A versatile approach for the synthesis of [1, 2, 4]triazolodipyrimidinones with various annulations of the triazole and pyrimidine rings was developed. The isomeric triazolodipyrimidinones were obtained by the stepwise condensation of partially hydrogenated [1, 2, 4]triazolo[1, 5- a ]pyrimidin-2-amines with β-ketoesters or diethyl ethoxymethylenemalonate, alkoxy base-mediated cyclization of the enamines, and subsequent cascade rearrangement of the 10-oxo-[1, 2, 4]triazolo[1, 5- a :4, 3- a ′]dipyrimidines.